The Use of Metaphor as a Tool in Depicting Tragedy in the Literary Works of Eugene O‟Neill - Ibrahim, Haider; Mohd Nawi , Abdullah; Ali, Ansam (International Journal of Psychosocial Rehabilitation, 2020)
The basic main of this article is to study the practice of metaphor in O’Neill’s chosen plays, especially in describing the catastrophic act. Evidence that there is some correlation in using metaphorical elements to show some painful scenes and actions. In this study, tragic images include issues of death, killing, sadness, and sexuality among the play’s masters, and figurative expressions include symbol, image, vanity, and Cantonese. The researcher shows how to use metaphor in describing tragic images in O’Neill’s plays.